HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH PADA SISWA PUTRA KELAS VIII SMP N 8 BENAI KABUPATEN KUANTAN SINGINGI - Meldi Herrman Meldi Herrman; Ramadi Ramadi '; Yuherdi Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract This research was conducted to determine whether there are relation of power leg muscle with long jump sport when making the leap so that when doing it can obtain maximum results. This research is a form of correlation study, which a population of male students clas VIII SMP Negeri 8 Benai Kuantan Singingi regency, consisted of 20 people. the data is processed with saturated sampling technique. The sample in this study is the all of the population, so that the sampel counted to 20 people. The istrument used in this study is test explosive power leg muscle with used standing broad jump instrument and long jump tests. after that, the data is processed with statistic, to test for normality with liliefors test at significant level. Hypothesis, there are relation of power leg muscle in the long jump results. Based on data analysis produced there are relation between power leg muscle (X) with long jump results (Y) of male students SMP Negeri 8 Benai Kuantan Singingi regency in the calculation produces 0,488 r count> 0,444 t table. There is relationship between power muscle leg (X) with long jump results (Y). It can be concluded that Ho is rejected and Ha is received, it shows that there is relationship between two variables.Keywords: power muscle leg and long jump